BIBLIOTHERAPY (TERAPI MELALUI BUKU) - -, Herlina (Edulib, 2012)
This account derives from various resources on basic concepts of bibliotherapy including its history, understanding, values, and limitations. Study on the basic concepts results in some explanation about the principles of bibliotherapy, the strategies of conducting bibliotherapy with accuracy based on the aim and its kind of problem faced. Results of the study will be beneficial for librarians, psychologists, and teachers who are interested in learning about how books serve as a tool needed by users, clients, or learners at large who have psychological troubles.